Effect of undergrowth-clearing on evergreen leaf litter decomposition and colonization by microarthropods (PEDOBIOLOGIA, 1996)
The effect of undergrowth-clearing has been studied for two years in a mediterranean Quercus ilex forest. The emphasis has been put on decomposition rate of Quercus ilex leaves placed in nylon bags and on microarthropod populations colonizing the litter bags. Undergrowth-clearing magnifies the characteristics of mediterranean climate but the differences of decomposition rate and microarthropod populations in cleared and uncleared sites are significantly different only in relation to local conditions. In the two situations, the rational and asymptotic models are those which fitted the decomposition rate the best. Seasonal variations of microarthropod populations in the four sites followed the response pattern of these generally observed in mediterranean regions. There was no correlation between litter mass loss and microarthropod numbers in bags. Data of this study were compared with those from nearby areas of Provence or mediterranean xerophilous ecosystems.

IMPACT OF CHRONIC GAMMA-IRRADIATION ON THE LITTER DECAY OF A MIXED MEDITERRANEAN FOREST IN CADARACHE - FRANCE MICROARTHROPODS RESPONSE (PEDOBIOLOGIA, 1995)
An area of mixed forest containing white oak (Quercus pubescens W.) and evergreen oak (Quercus ilex L.) in Cadarache has been irradiated for 16 years, since 1969, by a 137 cesium source of 31.45 TBq. Mass loss of experimental litter over a period of 22 months and its recolonization by soil microarthropods was studied at five stations receiving decreasing radiation levels (100 mGy/h(-1) to 0.3 mGy/h(-1)) and in a control area. At the end of the experimentation, the mass loss of the litter was substantially lower in the three most irradiated stations. Additionally recolonization of litter by microarthropods was low in these three stations compared with the three others. Population density of Oribatids, `'other Acarina'', Collembola and various Arthropods, was considerably lower. These results were dependant upon direct and indirect consequences of irradiation on the ecosystem. Destruction of trees and shrubs in the most irradiated areas (100-60 mGy/h(-1)) did in fact lead to the reduction of soil moisture and an absence of organic matter input. Microflora could not develop and insufficient trophic resources did not allow for recolonization by fauna, which in turn slowed down the eventual disappearance of the litter.

EFFECTS OF TANNIN COMPOUNDS ON 2 SPECIES OF COLLEMBOLA (EUROPEAN JOURNAL OF SOIL BIOLOGY, 1993)
The effects of condensed and hydrolysable tannin extracted from evergreen oak leaves (Quercus ilex L.) were tested on two species of Collembola. Concentrations lower than those present in the litter leaves were toxic to these insects. Detoxification by washing with rainwater and biodegradation of tannic compounds are necessary for litter decomposition, in which microarthropods participated, to occur.
Citation